A National Reckoning: Israeli Soldiers' Depictions of Wartime Trauma in Autobiographical Graphic Novels. (3rd July 2021) - Reingold, Matt
Abstract : The following paper analyses Ari Folman's 2009 graphic novel Waltz with Bashir and Galit and Gilad Seliktar's short graphic narrative 'Houses'. Each presents a visualization of an Israeli soldier forced to bear witness to a morally compromising event during their mandatory national service. The texts, while written within the last decade, depict wars from the 1980s and 1990s. Their narratives differ from the state-sanctioned versions of Israel's military as an army that always behaves morally. The works present an alternate narrative in which, at times, Israeli soldiers are expected to participate in immoral actions and that there is a lasting on their mental health. Additionally, when considered together, the two paint a portrait of an Israeli society that has not adequately responded to the strained emotions of segments of its population or found ways to bring these soldiers' feelings of self-doubt and self-recrimination into the national narrative of wartime experiences.